EUPATI and Patients in Medicines Research and Development: Guidance for Patient Involvement in Ethical Review of Clinical Trials - Klingmann, Ingrid; Heckenberg, Andrea; Warner, Kay; Haerry, David; Hunter, Amy; May, Matthew; See, Wolf (Frontiers in Medicine, 2018)
Patient participation in ethics committees is a much-discussed concept, its suitability disputed in many countries, and limited experience on best practices is available. Overarching guidance on meaningful and ethical interaction is missing. This “Guidance for patient involvement in ethical review of clinical trials” gives practical recommendations for conditions and practices of involving patients in the work of ethics committees. The guidance developed by the European Patients’ Academy on Therapeutic Innovation sets the collaboration of patients in ethics committees in the broader context of relevance and opportunities for patient engagement in ethical input in all clinical trial phases from trial concept development to trial result reporting in lay summaries.